Care in HIV drug trial closure: perspectives of research participants and staff in Uganda - Nalubega, Sylivia (2017)
Background: After three decades, Human Immunodeficiency Virus (HIV) continues to pose significant threats globally. The efforts to curb the HIV epidemic have required investment in research, with clinical trials being a major focus, to develop HIV prevention, treatment, and cure interventions. A large portion of such research has been undertaken within low income settings, due to the high burden of HIV and the availability of willing volunteers within this setting. HIV research calls for the implementation of ethical research practice which is informed by policy guidelines. However, current policies are largely informed by inputs from high income countries, and lack the voices of those closely involved in research implementation. In order to contribute to ethics policy development in HIV research, it is essential to involve different stakeholders by exploring their experiences/views on the issue. Existing research in this field has mainly explored experience of recruitment and trial conduct, while very little has been done on trial closure, indicating a significant evidence gap worth exploring. This research therefore sought to illuminate, explore and understand the significant issues regarding the care of HIV positive drug trial participants during closure of HIV clinical trials, within a low income setting, specifically, Uganda.